Bibliometric analysis of research areas, authors’ hierarchy and gender in German university gastroenterology and hepatology - Boklage, Katja; Debus, Sebastian; Lingenfelser, Thomas; Grundmann, Reinhart T. (Zeitschrift für Gastroenterologie, 2025)
This bibliometric study examines the publication activities of German university departments of gastroenterology and hepatology.First and last authorships from staff members (chief and consultants) of 39 German university departments of gastroenterology were evaluated. Gender assignment was carried out through manual verification based on information available on hospital websites. The observation period extended from 2010 to 2019, and all PubMed-listed publications were considered. The 5-year Impact factor (IF2016) was evaluated through the publishing journals’ five-year IF in 2016.A total of 4,923 publications with 22,609.5 cumulative impact factors (c-IFs) were generated by 509 staff members. Publications on gastroenterology accounted for 30.3% and publications on hepatology for 26.7% of the total publications. The most common research foci were therapeutic approaches (35.0%) and diagnostics (30.2%). While women comprised 21.8% of the total staff, they accounted for only 16.9% of publishing authors. The proportion of female staff decreased with increasing professional level (Consultants 26.2%, Consultants with management functions 12.7%, Directors 10%; Doctors 29.9%, Senior lecturers 13.9%, Professors 15.4%). The c-IF were distributed as 89% male and 11% female staff, with the average IF per authorship being nearly equal for male and female authorships (men IF 4.54, women IF 4.42).This study confirms the strong male dominance in leadership positions, number of publications, and generated c-IFs in German gastroenterological university departments.
Keywords: Statistics; Gastroenterology; Publication rate; University hospitals; gender specific differences; Impact factor; scientometric analysis